Butterfly Diversity of Indian Institute of Forest Management, Bhopal, Madhya Pradesh, India. (25th November 2014) - Harsh, Sprih
Abstract : A study to find out the diversity of butterflies at the Indian Institute of Forest Management (IIFM), Bhopal, was carried out over a period of six months from October 2013 to March 2014. A total of 55 butterfly species belonging to 5 families, namely, Hesperiidae (7 species), Papilionidae (4 species), Pieridae (10 species), Lycaenidae (13 species), and Nymphalidae (21 species), were recorded (with photographic record) during the study from three different habitats of campus: open scrub, dry deciduous, and urbanized habitat. Shannon diversity indices and Pielou's evenness index were calculated for all the habitats. Shannon index was found to be highest for open scrub (3.76). Out of 54 species, Eurema brigitta was the most dominant species followed by Eurema hecabe, Junonia lemonias, and Phalanta phalantha . Dominance of these species can be explained by the presence of their larval and host plants in the campus.